Whither Coronabonds? The Past and Future of the EMU in the Coronavirus Pandemic - Bodo Herzog (Intereconomics, 2020)
The long-term fiscal and economic damage of eurobonds in a rule-based fiscal architecture – as history corroborates – would be greater than the historical challenge of the coronavirus pandemic, unless there is a political union in Europe.
Keywords: 330